2022
DOI: 10.1093/pnasnexus/pgac198
|View full text |Cite
|
Sign up to set email alerts
|

Targeting an evolutionarily conserved “E-L-L” motif in spike protein to identify a small molecule fusion inhibitor against SARS-CoV-2

Abstract: As newer variants of SARS-CoV-2 continue to pose major threats to global human health and economy, identifying novel druggable antiviral targets is the key towards sustenance. Here, we identify an evolutionary conserved “E-L-L” motif present within the HR2 domain of all human and non-human coronavirus spike (S) proteins that play a crucial role in stabilizing its post-fusion six-helix bundle (6-HB) structure and thus, fusion-mediated viral entry. Mutations within this motif reduces the fusogenicity of the S pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…It can bind to the conserved “ E1182-L1186L-L1193 ” motif located in HR2 with high affinity, thereby interfering the 6-HB fusion core formation and then blocking membrane fusion. 119 In this way, Posaconazole can serve as a broad-spectrum fusion inhibitor against the ongoing SARS-CoV-2 variants. 119 In addition, itraconazole and estradiol benzoate could interact with the HR1 of several HCoVs, including SARS-CoV-2, SARS-CoV, and MERS-CoV, and exhibit broad neutralizing activity in vitro.…”
Section: Small-molecule Compounds That Block the Hr1-hr2 Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can bind to the conserved “ E1182-L1186L-L1193 ” motif located in HR2 with high affinity, thereby interfering the 6-HB fusion core formation and then blocking membrane fusion. 119 In this way, Posaconazole can serve as a broad-spectrum fusion inhibitor against the ongoing SARS-CoV-2 variants. 119 In addition, itraconazole and estradiol benzoate could interact with the HR1 of several HCoVs, including SARS-CoV-2, SARS-CoV, and MERS-CoV, and exhibit broad neutralizing activity in vitro.…”
Section: Small-molecule Compounds That Block the Hr1-hr2 Interactionmentioning
confidence: 99%
“… 119 In this way, Posaconazole can serve as a broad-spectrum fusion inhibitor against the ongoing SARS-CoV-2 variants. 119 In addition, itraconazole and estradiol benzoate could interact with the HR1 of several HCoVs, including SARS-CoV-2, SARS-CoV, and MERS-CoV, and exhibit broad neutralizing activity in vitro. 120 Meanwhile, biflavone-based anti-HIV drugs, such as hinokiflavone and robustaflavone, could prevent SARS-CoV-2 S-mediated virus entry by blocking the HR1-HR2 interaction.…”
Section: Small-molecule Compounds That Block the Hr1-hr2 Interactionmentioning
confidence: 99%
“…Pseudovirus entry assay was performed as described previously by Das Jana et al (2022) 22 . HEK 293T cells were transduced with lentiviral plasmids to express hACE2 protein.…”
Section: Pseudoviral Entry Assaymentioning
confidence: 99%
“…Hence, we tested their e cacy for inhibiting SARS-CoV-2 entry by using a pseudovirus-based entry assay. Previous reports indicated that HIV-1-based reporter lentiviruses with the re y luciferase ZsGreen reporter genes in their genomic backbone and SARS-CoV-2 spike protein as the sole surface glycoprotein are suitable for studying viral entry into host cells 21,42 . Therefore, we have generated reporter viruses pseudotyped with SARS-CoV-2 S and treated them with different aptamers before infecting HEK293T cells overexpressing ACE2 receptors (HEK293T-ACE2) (Fig.…”
Section: Thermodynamics Calculations Of Aptamer Rmentioning
confidence: 99%
“…For example, Itraconazole (ITZ) and Estradiol benzoate (EB), the clinically approved drugs for the treatment of patients with fungal infections and prostate cancer, respectively, can interact with the HR1 domain in S proteins of SARS‐CoV, MERS‐CoV, and SARS‐CoV‐2, thus inhibiting the entry and infection of these three HCoVs 44 . Posaconazole, an FDA‐approved antifungal drug, was reported to broadly inhibit fusion, entry, and infection of SARS‐CoV‐2 and its variants by binding the conserved E‐L‐L motif in the HR2 domain of SARS‐CoV‐2 responsible for stabilizing post‐fusion 6‐HB structure 45 . Some naturally occurring biflavone‐based anti‐HIV agents, for example, hinokiflavone and robustaflavone, could interact strongly with the residues in HR1 and HR2 regions of SARS‐CoV‐2 S protein and block the 6‐HB formation, thus inhibiting SARS‐CoV‐2‐target cell membrane fusion 46 .…”
Section: Development Of Pan‐cov Fusion Inhibitorsmentioning
confidence: 99%